Use of complementary and alternative medicines by a sample of Turkish women for infertility enhancement: a descriptive study - Kolusari Ali; Yildizhan Recep; Gucuk Sebahat; Arica Secil; Edirne Tamer; Adali Ertan; Can Muhammet (BMC, 2010)
Abstract Background Infertility patients are a vulnerable group that often seeks a non-medical solution for their failure to conceive. World-wide, women use CAM for productive health, but only a limited number of studies report on CAM use to enhance fertility. Little is known about traditional and religious forms of therapies that are used in relation to conventional medicine in Turkey. We investigated the prevalence and types of complementary and alternative medicine (CAM) used by infertile Turkish women for fertility enhancement. Methods A face-to-face questionnaire inquiring demographic information and types of CAM used for fertility enhancement were completed by hundred infertility patients admitted to a primary care family planning centre in Van, Turkey between January and July 2009. Results The vast majority of infertile women had used CAM at least once for infertility. CAM use included religious interventions, herbal products and recommendations of traditional "hodja's" (faith healers). Of these women, 87.8% were abused in the last 12 months, 36.6% felt not being supported by her partner and 80.5% had never spoken with a physician about CAM. Conclusions Infertile Turkish women use complementary medicine frequently for fertility enhancement and are in need of information about CAM. Religious and traditional therapies are used as an adjunct to, rather than a substitute for, conventional medical therapy. Physicians need to approach fertility patients with sensitivity and should be able to council their patients about CAM accordingly.